Greening City: Opportunities And Challenges in Workforce Development for A Sustainable Economy - Dian Widiyati; Jakaria Jakaria; Juniati Gunawan; Irene Stephanie Gow; Triniasi Eunike Sihombing; Hiemelda Gunawan; Gusti Made Widya Utami; Diska Mulyadini (Jurnal Ketenagakerjaan, 2025)
This study aims to investigates workforce readiness in Jakarta to adapt to green jobs as part of the broader transition toward a sustainable green economy. The research highlights the increasing urgency of addressing environmental challenges, such as climate change and pollution, by fostering sustainable development through green employment. The study employs a survey method involving 1,144 respondents from diverse demographic and educational backgrounds, analysing mental, behavioural, and skill readiness to adopt green jobs. Results indicate a high level of readiness for all three aspects. Mental readiness reflects strong awareness of environmental responsibility, though active engagement, such as reporting workplace violations, requires improvement. Behavioural readiness reveals support for sustainability initiatives, yet participation in labour unions remains low. Skill readiness demonstrates strong technical capabilities for sustainability practices, but stress management and interpersonal skills need enhancement. The study also identifies key sectors contributing to emission reductions, including agriculture, renewable energy, waste management, and construction, with varying potential across industries. Challenges persist, such as limited access to green technologies and insufficient stakeholder collaboration. Recommendations emphasize the integration of Green Human Resource Management, enhanced training programs, and supportive policies to accelerate green job creation and adoption. By fostering cooperation among government, industry, and education sectors, Jakarta can leverage its position as Indonesia's economic hub to pioneer sustainable practices and significantly contribute to global environmental goals.